Potensi Limbah Fly Ash PLTU Anggrek, Gorontalo Utara sebagai Bahan Substitusi Semen Pada Beton - Kadarningsih, Rahmani (Lambung Mangkurat University Press, 2024)
Accumulation of coal ash waste (fly ash) is a dangerous toxic material (B3) which light and fine so it easily flies in the air. This problem is urgent to be resolved because the production continues to increase in quantity and can cause air and water pollution. Currently, coal waste is used to make bricks, but research needs to be done on its potential as a concrete mixture and even as a cement substitute. Currently, coal waste is used to make bricks, but research necessery on its potential as a concrete mixture and even as a cement substitute. Therefore this research can be an alternative solution to the coal ash waste problem in Gorontalo Province. Research on the use of coal ash as a concrete mixture using crushed stone aggregate and sand from the quarry PT. CMP, Bonda Raya, South Suwawa To obtain a granular distribution that meets the requirements, the proportions used for crushed stone measuring 1-2 cm and measuring 2-3 cm are 65% and 35% respectively. Meanwhile, to obtain a combined gradation of fine and coarse aggregate that meets the requirements, percentages of 55% and 45% are used respectively. Based on the research results, the normal compressive strength value of concrete is 28.827 MPa. The compressive strength of fly ash variations of 5%, 10%, 15%, and 20% is 25,069 MPa, 27,442 MPa, 23,096 MPa, and 20,934 MPa. The compressive strength of fly ash variations is lower than normal concrete. The optimum compressive strength value for fly ash substitution for cement with a 10% variation is 27.442 MPa.